2021
DOI: 10.1016/j.bbrep.2021.101175
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evaluation and molecular docking assessment of Cymbopogon citratus as a natural source of acetylcholine esterase (AChE)- targeting insecticides

Abstract: Acetylcholinesterase (AChE) has been an effective target for insecticide development which is a very important aspect of the global fight against insect-borne diseases. The drastic reduction in the sensitivity of insects to AChE-targeting insecticides like organophosphates and carbamates have increased the need for insecticides of natural origin. In this study, we used Drosophila melanogaster as a model to investigate the insecticidal and AChE inhibitory potentials of Cymbopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…2b indicate clearly that the EO from T. riparia, fenchone, and α-cypermethrin triggered a signi cant increase of activity this enzyme in C. quinquefasciatus larvae when compared with DMSO (F 3.8 = 285.3; p < 0.05). These ndings corroborate with other studies which reported increase in CAT activity in D. melanogaster after exposing to extract at 200 mg/mL from Cymbopogon citratus (Poaceae) (Johnson et al 2021), 4vinylcyclohexene 1,2-monoepoxide, and 4-vinylcyclohexene diepoxide (Abolaji et al 2015). Conversely, some insecticides with systemic action, such as neonicotinoid cause the death of insects without inducing alterations in the activity of catalase (Eruslanov and Kusmartsev 2010).…”
Section: Catalase Activity (Cat)supporting
confidence: 91%
See 1 more Smart Citation
“…2b indicate clearly that the EO from T. riparia, fenchone, and α-cypermethrin triggered a signi cant increase of activity this enzyme in C. quinquefasciatus larvae when compared with DMSO (F 3.8 = 285.3; p < 0.05). These ndings corroborate with other studies which reported increase in CAT activity in D. melanogaster after exposing to extract at 200 mg/mL from Cymbopogon citratus (Poaceae) (Johnson et al 2021), 4vinylcyclohexene 1,2-monoepoxide, and 4-vinylcyclohexene diepoxide (Abolaji et al 2015). Conversely, some insecticides with systemic action, such as neonicotinoid cause the death of insects without inducing alterations in the activity of catalase (Eruslanov and Kusmartsev 2010).…”
Section: Catalase Activity (Cat)supporting
confidence: 91%
“…As a component of the antioxidant defence system of insects, the enzyme CAT plays a crucial role in catalyzing the conversion of hydrogen peroxide (H 2 O 2 ) into water (H 2 O), and molecular oxygen (O 2 ), this process helps prevent the overproduction of RONS, and H 2 O 2 , maintaining redox balance under control (Johnson et al 2021). Furthermore, the CAT also acts in protecting the insect organism against toxic agents, such as botanical larvicides, that can lead to the death of the organism (Shahriari et al 2018).…”
Section: Catalase Activity (Cat)mentioning
confidence: 99%
“…The atomic coordinates of the crystal structures of the target enzyme, acetylcholine esterase (AChE) with the PDB ID of 2ACE, were downloaded from the protein databank. Before docking or doing any analysis, the target structures had polar hydrogen atoms added to them, and any accessible water molecules, native ligands, and undesirable chains were eliminated 51 . With regard to the other parameters, the default values were implemented 52 , 53 .…”
Section: Methodsmentioning
confidence: 99%
“…The Signalp-5.0 (http://www.cbs.dtu.dk/services/SignalP/) was performed for prediction in the location of a signal peptide. Additionally, the molecular interaction of TcGSTe17 with eucalyptol was preliminarily analyzed by Schrodinger (Johnson et al 2021). The underline of dsRNA primers is T7 promoter sequence.…”
Section: Gene Clone Bioinformatics Analysis and Molecular Interactionmentioning
confidence: 99%
“…5), indicating that GST activity of T. castaneum was inhibited after exposure to eucalyptol. Generally, the activity of GST enzyme was signi cantly increased after exposure to insecticides (Johnson et al 2021) or in insecticide-resistant strain (Hu et al 2022). However, the activity of GST enzyme in T. castaneum was inhibited after exposure to eucalyptol, which is consistent with previous results that eucalyptol can reduce activities of Rhipicephalus microplus GST enzyme at the highest concentration (Yang et al 2021).…”
Section: Expression Pro Le Of Tcgste17mentioning
confidence: 99%